2013
DOI: 10.1177/0025802413477396
|View full text |Cite
|
Sign up to set email alerts
|

Screening for synthetic cannabinoids in hair by using LC-QTOF MS: A new and powerful approach to study the penetration of these new psychoactive substances in the population

Abstract: The current analytical technology for the determination of New Psychoactive Substances in biological samples is still largely inadequate, because the immunoassays are unsuitable for the detection of most of these compounds and the use of traditional gas chromatography-mass spectrometry techniques is hampered by the lack of chromatographic standards and mass fragmentation patterns. Taking advantage of the molecular recognition capability of high-resolution mass spectrometry, the present work aimed to apply liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…In SCs extraction, LLE is usually used because of their high hydrophobicity. It has been used for the extraction of SCs in the following matrices: blood [35,[66][67][68][69][70][71][72], serum [39,[73][74][75][76], plasma [77], urine [40,41,47,49,51,59,72,[78][79][80][81][82][83], oral fluid [84,85] and hair [86][87][88][89][90]. It involves adding an immiscible organic solvent such as tert-butyl methyl ether [41,82], chloroform [50] and diethyl ether [40,52,79] to the sample, and mixing, removing the organic solvent.…”
Section: Liquid-liquid Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SCs extraction, LLE is usually used because of their high hydrophobicity. It has been used for the extraction of SCs in the following matrices: blood [35,[66][67][68][69][70][71][72], serum [39,[73][74][75][76], plasma [77], urine [40,41,47,49,51,59,72,[78][79][80][81][82][83], oral fluid [84,85] and hair [86][87][88][89][90]. It involves adding an immiscible organic solvent such as tert-butyl methyl ether [41,82], chloroform [50] and diethyl ether [40,52,79] to the sample, and mixing, removing the organic solvent.…”
Section: Liquid-liquid Extractionmentioning
confidence: 99%
“…The main challenge of non-targeted LC-HRMS screening methods is to achieve sufficient selectivity to identify low concentrations of SC [19]. Several non-targeted methods using HRMS technique for screening of drugs of abuse including SCs in biological matrices were published [89,94,114,115]. These methods are enabling forensic laboratories to obtain accurate data of MS and MS/MS without pre-selecting substances.…”
Section: Analytical Challenges and Solutionsmentioning
confidence: 99%
“…Thus, whereas the determination of synthetic cannabinoids in urine and blood will therefore be faced with the issue of identifying several metabolites often not well known, hair analysis can be focussed directly on the parent drug. Nevertheless, to date, only few studies deal with the determination of NPS in hair [19][20][21][22][23][24]. Two studies reported in the recent literature for the determination of synthetic cannabinoids used extraction methods based on incubation in concentrated sodium hydroxide solutions, providing the dissolution of the keratin matrix [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic cannabinoids, often referred to as ''cannabinoid receptor agonists'', are relatively new analytes in hair analysis with only a few methods published in the literature so far [1][2][3][4]. This category of drugs was first identified in 2008 in Germany and Japan [5,6]; these novel psychoactive substances (NPS) mark the largest group of compounds reported through the Early Warning System of the European Monitoring Centre for Drugs and Drug Addiction (EMCCDA) in the past few years, with 30 new compounds in 2012 [7] and 29 in 2013 [8].…”
Section: Introductionmentioning
confidence: 99%